2005
DOI: 10.1300/j074v17n01_04
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study of Exercise in Older African American and White Women in Rural South Carolina: Perceptions, Barriers, and Motivations

Abstract: Six focus groups were conducted with underactive African American (n = 16) and white (n = 23) women aged 50 years and older, residing in a nonmetropolitan county in South Carolina, to examine perceptions, barriers, and motivators related to exercise. Transcripts were coded and codes were entered into NUD*IST to assist with organizing and reporting themes. Participants could not reach consensus on the frequency, intensity, and duration of exercise needed for older women, and emphasized that PA recommendations s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
120
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(138 citation statements)
references
References 16 publications
11
120
1
3
Order By: Relevance
“…This finding has also been reported in the literature on older adults 26,27 and cardiac rehabilitation, 28 where participants expressed concerns regarding exercise as potentially harmful by causing breathlessness (ie, negative outcome expectations). Along with mastery experience, other sources of self-efficacy such as vicarious experience, verbal persuasion, and physiological state would be important to consider in this context.…”
Section: Discussionsupporting
confidence: 78%
“…This finding has also been reported in the literature on older adults 26,27 and cardiac rehabilitation, 28 where participants expressed concerns regarding exercise as potentially harmful by causing breathlessness (ie, negative outcome expectations). Along with mastery experience, other sources of self-efficacy such as vicarious experience, verbal persuasion, and physiological state would be important to consider in this context.…”
Section: Discussionsupporting
confidence: 78%
“…Community places include areas and organizations such as community centers, schools, worksites, places of worship, and other common facilities in rural communities such as volunteer fire houses. These places may be important settings for planned and spontaneous physical activity [81,83]. Future research is needed to better understand these community resources, since current research is either completely absent or focuses on programming or wellness approaches rather than the built environment [75,[84][85][86][87].…”
Section: Community Placesmentioning
confidence: 99%
“…These results are consistent with many studies which confirmed that the dissemination of the culture of health promotion contributes to improving the health status of patients and the prevention of complications of disease. [22,23,24] In contrast to other studies of barriers in women, which stated that overlapping responsibilities in women are important barriers as the presence of many responsibilities reduce their concern for their health. [25,26,27,28] The current study revealed that a highly significant association was detected between the levels of Health Promotion Barriers and type of chronic disease.…”
Section: Discussionmentioning
confidence: 99%